2019
DOI: 10.1002/phar.2276
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Relapsed Chronic Subdural Hematoma in Four Young Children with Atorvastatin and Low‐dose Dexamethasone

Abstract: Chronic subdural hematoma (CSDH) can develop in children in rare cases. Burr‐hole drainage (BHD) is the treatment of choice, but it is associated with a high rate of recurrence. This report describes four cases of pediatric patients (1–7 yrs of age) with post‐BHD relapsed CSDH who were successfully treated with a drug regimen that included 2.5–5 mg atorvastatin daily combined with dexamethasone with stepwise‐decreasing dosing for a total of 4 weeks. After 4 weeks of treatment, the hematoma was completely resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
1
11
0
4
Order By: Relevance
“…8 Our recent study with four young patients indicated that atorvastatin combined with low-dose dexamethasone treatment completely cured three of the patients and obviously decreased the hematoma size in the remaining patient without any clinical complications. 9 Additionally, with our further proof-of-concept Phase II clinical trial, we showed that atorvastatin combined with low-dose dexamethasone treatment is more effective than atorvastatin alone in reducing the hematoma size and improving neurological function in patients with CSDH. 10 Moreover, the results of our basic research study were the same as those of our clinical study.…”
Section: Introductionmentioning
confidence: 76%
“…8 Our recent study with four young patients indicated that atorvastatin combined with low-dose dexamethasone treatment completely cured three of the patients and obviously decreased the hematoma size in the remaining patient without any clinical complications. 9 Additionally, with our further proof-of-concept Phase II clinical trial, we showed that atorvastatin combined with low-dose dexamethasone treatment is more effective than atorvastatin alone in reducing the hematoma size and improving neurological function in patients with CSDH. 10 Moreover, the results of our basic research study were the same as those of our clinical study.…”
Section: Introductionmentioning
confidence: 76%
“…Within the context of CSDH, atorvastatin, in particular, was investigated in numerous studies and was repeatedly found to improve the clinical course. The published articles ranged from small case series [ 1 , 5 ] to larger studies [ 6 , 20 , 25 ] and two randomized controlled trials (RCT) [ 7 , 22 ]. Notably, two positive studies were later retracted [ 9 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another randomized, placebo-controlled, double-blind phase II clinical trial reported that atorvastatin reduces hematoma, and improves neurological function and quality of life; the effect persisted for a follow-up period of 16 weeks in nonsurgical patients with subdural hematoma (Jiang et al, 2018). In addition, Huang et al found that atorvastatin combined with dexamethasone is a safe and effective option for the treatment of pediatric patients with recurrent subdural hematoma (Huang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%